The camping life : inspiration and ideas for endless adventures - Leonard, Brendan; Woodward, Forest (Artisan, 2020)
"From roughing it in the Mojave Desert without a tent to glamping in a cozy cabin in the Adirondacks, camping for pleasure is undeniably more popular than ever before. And all the while, the definition of camping is being refined and expanded to include a plethora of experiences. Because as we saw with Artisan's The Campout Cookbook, people want more from their camping experiences-including good meals, a comfy sleeping experience, and some epic sunsets to document on Instagram. The Camping Way captures the feeling and aesthetic of sleeping under the stars and peels back the curtain to show readers how it's all done-from camping while suspended on a mountainside to camping while on a kayak or bike trip. Each type of adventure is told through photography showing beautiful vistas, campsites and setups, close-up explanatory vignettes, and informative text. Essays and illuminating deep captions truly capture the camping experience. Additional text includes recommended locations for each type of experience and for all budgets, and how-to skills to show readers how to pack, carry, cook, and leave no trace like an expert camper. The Camping Way is for both armchair campers and those ready to rough it, and shows that there are many ways to explore the outdoors"--